The role of vitamin D in metabolism and bone health : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Albany, New Zealand - von Hurst, Pamela Ruth (Massey University, 2009)
Background Hypovitaminosis D is becoming recognised as an emerging threat to health, even in countries like New Zealand which enjoy plentiful sunshine. The evidence for a role for vitamin D deficiency in the aetiology of a plethora of diseases continues to accumulate, including type 2 diabetes, and the preceding insulin resistance. Objectives The primary objective of the Surya Study was to investigate the effect of improved vitamin D status (through supplementation) on insulin resistance. The secondary objectives were to investigate the vitamin D status and bone mineral density of South Asian women living in New Zealand, and to investigate the effect of vitamin D supplementation on bone turnover as measured by biochemical markers of bone resorption and formation. Method Women of South Asian origin, ≥20 years old, living in Auckland (n = 235) were recruited for the study. All were asked to complete a 4-day food diary, invited to have a bone scan, and were screened for entry into the intervention phase which required insulin resistance (HOMA-IR >1.93) and serum 25(OH)D < 50 nmol/L. Eighty-one completed a 6-month randomised controlled trial with 4000 IU vitamin D3 (n = 42) or placebo (n = 39). Primary endpoint measures included insulin resistance, insulin sensitivity (HOMA2%S), fasting C-peptide and markers of bone turnover, osteocalcin (OC) and collagen C-telopeptide (CTX). Ninety-one of the 239 had a bone scan and bone mineral density (BMD) was measured in the proximal femur and lumbar spine. Results Adequate serum 25(OH)D concentrations (>50 nmol/L) were observed in only 16% of subjects screened. Median (25th, 75th percentile) serum 25(OH)D increased significantly from 21 (11,40) to 75 (55,84) nmol/L with supplementation. Significant improvements were seen in insulin sensitivity and insulin resistance (P = 0·003, P = 0·02 respectively), and circulating serum insulin decreased (P = 0·02) with supplementation compared to placebo. There was no change in C-peptide with supplementation. Insulin resistance was most improved when endpoint serum 25(OH)D =80 nmol/L. In post-menopausal women OC and CTX levels increased in the placebo arm but CTX decreased from 0.39±0.15 to 0.36±0.17 (P = 0.012) with supplementation. Osteoporosis (T score <-2.5) was present in 32% of postmenopausal, and 3% of premenopausal women. Women 20 – 29 years (n=10) had very low BMD, calcium intake and serum 25(OH)D Conclusions Improving vitamin D status in insulin resistant women resulted in improved insulin resistance and sensitivity but no change in insulin secretion. Optimal 25(OH)D concentrations for reducing insulin resistance were shown to be ≥80 nmol/L. The prevalence of low 25(OH)D concentrations in this population was alarmingly high, especially in younger women. In post-menopausal women, vitamin D supplementation appeared to ameliorate increased bone turnover attributed to oestrogen deficiency.
Keywords: Vitamin D; Insulin sensitivity; Insulin resistance; Osteoporosis; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321205 Nutrition and dietetics